Low cost cylindrical lumen testing procedure in Bangladesh perspective - Khan, S. A.; Rahman, Rifat; Shabnam, Farah; Azad, Dr. Md. AKM Abdul Malek (© 2013 IEEE Computer Society, 2016)
This conference paper was presented in the 3rd IEEE Global Humanitarian Technology Conference, GHTC 2013; San Jose, CA; United States; 20 October 2013 through 23 October 2013 [© 2013 IEEE Computer Society] The conference paper's definite version is available at: http://10.1109/GHTC.2013.6713658